Synthesis of 1,2,4-Dinitro Phenyl-3-p-Hydroxy, 3-Methoxy Phenyl-5-2-Naphthol-4-Sulphonyl Formazan Dye - Sahai, V.M.; Joshi, Deepak; Dubey, Rashmi (Asian Journal of Chemistry, 2010)
Formazan dye has been synthesised from diazonium salt of 1-amino, 2-napthol, 4-sulphonic acid coupling with active hydrogen present in 3-methoxy, 4-hydroxy benzaldehyde phenyl hydrazone.